Effect of Tail Configuration Variation and Stability Level on Battery Performance in Unmanned Aerialvehicles (UAV) - Belia Alfiko; Agus Nur Cahyo; Heru Susanto (International Journal of Mechanical, Industrial and Control Systems Engineering, 2025)
This study investigates the impact of tail configuration variations on flight stability and battery energy efficiency in Unmanned Aerial Vehicles (UAVs). Three distinct tail types were tested: the conventional tail, the T-Tail, and the V-Tail. The objective was to compare how these tail designs affected the overall performance of UAVs, especially focusing on the balance between stability and energy efficiency. The experiments were conducted through a series of flight tests in a controlled outdoor environment, providing reliable and accurate data. During these flight tests, several performance metrics were recorded, including IMU-based angular deviations for pitch, roll, and yaw, energy consumption, flight time, voltage, and battery power. The data collected allowed for a thorough analysis of how the tail design influenced the flight characteristics of the UAVs. The results showed that the T-Tail configuration provided the highest flight stability, as indicated by the smallest angular deviations and minimal vibration during flight. This design’s enhanced stability made it the most reliable, especially for missions requiring precision control. In contrast, the V-Tail configuration proved to be the most energy-efficient, consuming only 22.80 Wh. Despite its low energy consumption, the V-Tail showed the lowest stability due to control coupling between the pitch and yaw axes, resulting in higher angular deviations and less precise control. The conventional tail, while not the best in terms of either stability or energy efficiency, struck a reasonable balance between the two. This configuration provided adequate stability while ensuring efficient battery usage, making it a suitable choice for general UAV applications. The findings of this study highlight the direct influence of tail design on UAV performance. There is a clear trade-off between flight stability and energy efficiency, with the conventional tail offering the best compromise.